The Boma: Sarah Nyakeri talks about vulnerability in science? - International Livestock Research Institute (International Livestock Research Institute, 2022)
"I’ve learned that using the simplest words doesn’t make you less of a scientist. It can actually make you a great scientist." Sarah Nyanchera Nyakeri is an MSc fellow at the International Livestock Research Institute where she is researching the development of a better vaccine for contagious bovine pleuropneumonia (CBPP). She is also the winner of the recent ILRI CapDev challenge which seeks to find the best science communicators amongst the next generation of livestock researchers. She is also the host and producer of 'The Vulnerable Scientist' podcast which focuses on scientists' stories about their daily lives, work, and how they got to where they are. From one podcaster to others, Elliot Carleton and Brenda Coromina talk to Sarah to find out more about her podcast, and what it unexpectedly reveals about being a scientist. This special interlude episode touches on failures, being a woman in science, role models in science, and more. Don't forget to check out Sarah's podcast afterwards!